IMPLEMENTATION D’UNE APPLICATION INFORMATIQUE DISTRIBUEE POUR LA GESTION DE PRESTATIONS DE L’OFFICE CONGOLAIS DE CONTROLE - DIOR - ONGEMBE, Joseph LOLEKE (IJRDO -Journal of Computer Science Engineering, 2023)
Now a days, one of the most envy trend and which concern all the development sectors, is the information. Since the appearance of IT and its introduction into the economic world, companies and public entities aspire to optimize and make reliable management of their internal structure. In this article, we take stock of the construction of a distributed application that is based on adapted software architects. The OCC being one of the large companies in the province, must be  based on new technologies to improve the quality, speed, security of transmitting services rendered to its customers and a tool capable of profitable its current management which is still manual. The objective of this article is to define the analytical the analytical and conceptual steps of a distributed computer application based on the server side restructuring technology consume by a mobile application under Android allowing this company to have a system adapted to its needs and that is directly related to the REST of its computer equipment.